Key Factors Influencing Customer Satisfaction and Repurchase Intentions on Online Shopping Platforms in Chengdu, China - Qing, Li (Scholar: Human Sciences, 2025)
Purpose: This paper aimed to investigate the key factors that substantially impact online shopping satisfaction and repurchase intention of three majors at a university in Chengdu, China. Research design, data, and methodology: Information quality, system quality, benefits, customer support, packaging, trust, satisfaction, and repurchase intention were all interconnected in the conceptual framework. The researchers selected undergraduate students from three majors in the same college as the target university and collected 500 samples through questionnaires for quantitative research strategies. This paper adopts the multi-stage sampling strategy to collect data, using judgment and purposive sampling. Confirmatory factor analysis (CFA) and structural equation model (SEM) were used to analyze the data, and the model's goodness of fit, correlation validity, and reliability were tested for each variable. Results: Each variable proved to have significant direct or indirect effects on satisfaction and repurchase intention. Trust was the most significant and directly affected the dependent variable, and the second and third variables affecting satisfaction were benefits and information quality. In addition, satisfaction has a significant effect on repurchase intention. Conclusions: This study supplements the factors affecting online shopping satisfaction and repurchase intention from the perspective of impartial trust. It provides a more novel evaluation index of online shopping satisfaction and repurchase intention.